0359 A One Year Study Of 1, 069 Good Sleepers: The Incidence Of Acute And Chronic Insomnia. (27th April 2018) - Gencarelli, A M; Khader, W; Morales, K; Vargas, I; Grandner, M A; Ellis, J; Kloss, J D; Perlis, M L
Abstract: Introduction: While there is a wealth of data regarding Insomnia prevalence, little is known about incidence rates for transitions from Good Sleep (GS) to Acute Insomnia (AI) and from AI to Persistent Poor Sleep (PPS), Chronic Insomnia (CI) or Recovery back to GS. The lack of such data prohibits the assessment of how commonly AI occurs on a per annum basis and the extent to which subjects recover from such episodes or go on to develop persistent or chronic insomnia. In 2017, we completed data collection on a national cohort of 1, 069 subjects who were recruited and corroborated as good sleepers (good sleep over the course of the first 3 months of the study). In addition to other measures given on a periodic basis, subjects were monitored over one year's time with daily sleep diaries. Methods: Using daily sleep diary data, groups were identified by "transition" (AI, REC, PPS, or CI), defined as follows: AI : 2 consecutive weeks with a frequency of ≥3 nights/week of SL and/or WASO severity > 30min; REC : 12 consecutive weeks of good sleep after AI and/or CI; PPS : recurring bouts of AI without transition to CI or REC; and CI : 12 consecutive weeks with same freq/severity criteria as AI. Results: The incident rate of AI was 19.2%. Of these 205 subjects, (45.4%) recovered good sleep, 93 (45.4%) exhibited persistently poor sleep but did not meet criteria for chronic insomnia, and 19 (9.3%) developed CI. No significant between-group differences were observed for demographic variables (race, age, sex, BMI, or income). Conclusion: These data suggest that acute insomnia is common and that about half of the affected subjects recover. Work is underway to assess what factors predict recovery (resilience) and non-recovery (persistent poor sleep or the new onset of chronic insomnia). Support (If Any): Acknowledgements: Perlis: NIH R01AG041783 & Ellis: Economic and Social Research Council (RES-061-25-0120-A).